Corruption as a social determinant of Mental Health: Levels and clinical correlates - Sarabia, Silvana (2025)
Corruption is a complex concept, part of several fields of knowledge, study and research areas, and individual, collective, social and institutional behaviors, also delineated by philosophical-existential and religious-spiritual perspectives. This article attempts to explore such ontological diversity to make possible a focus on corruption as a social determinant of Health and Mental Health, its characteristics and implications on individual and community-based behaviors, with emphasis on assumptions and clinical formulations (as symptom, syndrome or a crucial component of nosological-psychiatric categories, social origins and bureaucratic-administrative practices. Its impact on mental health and mental illness, interactions with resilience and other factors precede management postulates at various levels and imply, as well, the eventual elaboration of possible preventive norms.